Molecular basis of EphA2 recognition by gHgL from gammaherpesviruses - Chao Su (Nature Portfolio, 2020)
EphA2 is the specific entry receptor for both human γ-herpesviruses Kaposi sarcoma associated herpesvirus (KSHV) and Epstein-Barr virus (EBV). Here, the authors present the crystal structures of the EphA2 ligand binding domain (LBD) bound to the viral glycoprotein gHgL from EBV and KSHV and further analyse EphA2 gHgL interactions with mutagenesis experiments in cell-based fusion assays and suggest that other animal γ-herpesviruses could also use EphA2 as an entry receptor.